Reliability analysis on key processes of bakery-product operations. (21st March 2011) - Vasileiou, Christos C.; Besseris, George J.
In this paper, a reliability and maintainability analysis concerning several automated mechanical equipments in three bakery production lines in Vivartia S.A. is presented. Failed machine forces upstream line at the point where the failure appeared to operate without material processing whereas the material itself (raw, intermediate or end-product) of the downstream line may be scrapped due to a down-graded quality level. Based on collected data pertaining past failures, descriptive statistics of failure and repair data, the identification of the most important failure modes, and the determination of the most suitable theoretical distributions parameters to be applied were determined. Furthermore, key reliability parameters for the examined production machinery were obtained. The reliability analysis that we undertook may prove to be useful as a case study in evaluating reliability concerns leading to the development of an improved maintenance policy in equipments associated with the baking industry. Moreover, maintenance engineers in food industry may be benefited from this report when designing and analysing overall equipment efficiency.